Osteology of a forelimb of an aetosaur Stagonolepis olenkae (Archosauria: Pseudosuchia: Aetosauria) from the Krasiejów locality in Poland and its probable adaptations for a scratch-digging behavior - Dróżdż, Dawid (PeerJ, 2018)
Aetosaurs are armored basal archosaurs that played a significant role in land ecosystems during the Late Triassic (237–201 Ma). The polish species Stagonolepis olenkae Sulej, 2010 described from the Krasiejów locality (southern Poland) is one of the oldest known representatives of the group. Abundant and well-preserved material, including partially articulated specimens, allows a detailed description of the forelimbs in this species. The forelimbs of S. olenkae are the most similar to that of large aetosaurs like Desmatosuchus smalli, Desmatosuchus spurensis, Longosuchus meadei, Typothorax coccinarum or Stagonolepis robertsoni. Several characters recognized in the forelimbs of S. olenkae suggest its adaptation for scratch-digging. The most salient of these features are: short forearm, carpus, and hands, with the radius shorter than the humerus, carpus and manus shorter than the radius (excluding terminal phalanges); a prominent deltopectoral crest that extends distally on the humerus and a wide prominent entepicondyle, a long olecranon process with well-marked attachment of triceps muscle; hooked, laterally compressed, claw-like terminal phalanges with ornamentation of small pits (indicative of well-developed keratin sheaths). S. olenkae might have used its robust forelimbs to break through the compacted soil with its claws and proceed to dig in search of food in softened substrate with the shovel-like expansion at the tip of its snout. The entire forelimb of S. olenkae is covered by osteoderms, including the dorsal surface of the hand, which is unusual among aetosaurs and have not been noted for any species up to date.
Keywords: Aetosauria; Manus; Archosauria; Scratch-digging; Forelimb; Carpus; Krasiejów